Analisis Sensor Arus Invasive ACS712 dan Sensor Arus Non Invasive SCT013 Berbasis Arduino - wayan arsa suteja; adi surya antara (Program Studi Teknik Elektro Universitas Khairun, 2021)
The electric load measurement system is a device designed to measure and monitor electricity consumption. In this research, the comparison process of reading the electric current uses the Non-Invasive current sensor model SCT013 and the Invasive current sensor model ACS712 which is connected to the load of electricity consumption. The microcontroller used is the Arduino Microcontroller which functions as the main control system that will be connected to the computer. With the aim later to be able to determine which current sensor is suitable and accurate in reading the electric current. By conducting experiments on the variables of two current sensors, in order to obtain the results of the comparison of the measurement and monitoring of the non-invasive current sensor model SCT013 with the Invasive current sensor model ACS712. Researchers hope to get how much the error percentage value or error of two non-invasive current sensors model SCT013 with Invasive current sensor model ACS712, so that later we can find the right sensor to get the right data for measuring tools, and can be used to monitor energy consumption. electricity that we use